Contrasting Immunomodulatory Effects of Probiotic and Pathogenic Bacteria on Eastern Oyster, Crassostrea Virginica, Larvae - Tejashree H. Modak; Marta Gomez-Chiarri (Vaccines, 2020)
Several Vibrio spp. cause acute and severe mortality events in hatcheries where larvae of bivalve mollusks are reared, potentially leading to subsequent shortage of bivalve seed for the grow-out industry. In particular, strains of Vibrio coralliilyticus have been identified as a major cause of disease in Pacific, Crassostrea gigas, and eastern, C. virginica, oyster hatcheries in the USA of America. Probiotic bacteria are an inexpensive, practical, and natural method of disease control. Previous research shows that pretreatment of larval oysters with probiotic bacteria Bacillus pumilus RI06–95 (RI) and Phaeobacter inhibens S4 (S4) significantly decreases mortality caused by experimental challenge with the bacterial pathogen V. coralliilyticus RE22 (RE22). This study aims to characterize the immune response of 6–10-day-old eastern oyster larvae to experimental challenge with pathogen V. coralliilyticus RE22 and probionts RI and S4. Treatments included (a) pathogen and probiont exposure at a concentration of 5 × 104 CFU per mL (~2500 bacterial cells per larva) for a duration of 6 h, (b) probiont exposure at the same concentration for a duration of 24 h, and (c) probiont RI daily treatment of larvae in the hatchery for 4, 11, and 15 days. Differential gene expression analysis compared pathogen or probiotic-treated transcriptomes to unexposed controls. Probiotic and pathogen treatment led to upregulation of transcripts coding for several immune pattern recognition receptors (PRRs) involved in environmental sensing and detection of microbes in oyster larvae. Larval oyster responses to pathogen RE22 suggested suppression of expression of genes in immune signaling pathways (myd88, tak1, nkap), failure in upregulation of immune effector genes, high metabolic demand, and oxidative stress that potentially contributed to mortality. On the other hand, the transcriptomic response to probiotic bacteria RI and S4 suggested activation of immune signaling pathways and expression of immune effectors (e.g., Cv-spi2, mucins and ...